Large Quiet Road — the Forgotten Art of the Estonian Sculptor August Timus - Kuldna, Kersti; Khmelnitskaya, Ekaterina S. (Actual Problems of Theory and History of Art, 2013)
The article provides an overview of the main works of Estonian sculptor August Timus who was the chief sculptor of the Imperial Porcelain Factory in St. Petersburg at the turn of the 19th ‒ 20th cc. A special attention is paid to the work of the sculptor after 1917 when he had to leave Russia and return to Estonia.
Keywords: August Timus; porcelain; sculpture; Imperial Porcelain Factory in St. Petersburg emigration; Estonia